Faktor-Faktor Yang Mempengaruhi Produksi Bawang Daun (Allium Fistulosum L.) di Kecamatan Wanaraya Kabupaten Barito Kuala - Pertiwi, Ria Anita; Aulia , Redhana; Achmad Ramadhan; Sarbaini; Maulida Murdayanti; Almaisarah, Almaisarah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
Farmers must do everything they can to achieve maximum leek production, namely by utilizing production factors effectively and combining them optimally. In fact, many farmers do not know how to use and combine production factors appropriately. The purpose of this study was to analyze production factors that influence leek production and identify problems faced by farmers and solutions to overcome them in leek farming in Wanaraya District. The data analysis method used was multiple linear regression analysis and descriptive analysis. The results showed that the factors that significantly influenced leek production were planting area, while the variables of seeds, fertilizers, pesticides, and labor did not significantly influence leek production in Wanaraya District. Problems faced by farmers in leek farming in Wanaraya District include high rainfall that can cause plant rot, as well as pest and disease attacks that reduce productivity such as stem-eating caterpillars and fusarium wilt disease.